Native Web Communication Protocols and Their Effects on the Performance of Web Services and Systems - Naik, Nitin; Jenkins, Paul; Davies, Philip; Newell, David (2016 IEEE International Conference on Computer and Information Technology (CIT), 2016)
Native Web communication protocols are the pivotal components of Web services, applications and systems. In particular, HTTP is a de facto protocol standard used in almost all Web services and systems. Consequently, it is one of the crucial protocols responsible for the performance of Web services and systems. HTTP/1.1 has been successfully deployed in Web services and systems for the last two decades. However, one of the most significant issues with HTTP/1.1 is the Round Trip Time and Web latency. To resolve this issue, two successor protocols SPDY and HTTP/2 have been developed recently, with some studies suggesting that SPDY improved the performance of Web services and systems, whilst some did not find significant improvements in the performance. HTTP/2 is a relatively new protocol and has yet to be tested with any rigour. Therefore, it is important to investigate the effects of these two enhanced protocols SPDY and HTTP/2 on the performance of Web services and systems. This paper conducts a number of practical investigations to evaluate the performance of Web services and systems with and without the support of SPDY and HTTP/2 protocols at the client and server. This study investigates the impact of SPDY and HTTP/2 on the overall performance of Web services and systems from the end-user's perspective.